SIMBOLISME FONETIS NAMA BINATANG DALAM BAHASA MANDARIN - Budi Santoso (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2008)
Chinese society represent their idea, concept, and values through certain symbol realized in picture or other things. Animal, as one of symbols, plays an important role compared to plant. The use ofanimal as a symbol is determined not only because of the similarity of its characteristics but also because of the similarity of phonetic sound. This kind of symbol is called phonetic symbol. The use of phonetic symbol in animal’s name occurs because Chinese language has a few syllables. It causes Chinese language have a number of homophone, so one syllable represents several concepts. Because of the similarity of phonetic sound, Chinese society, then, use an animal to symbolize a certain concept due to the similarity of sound between the name of the animal and the concept.Keywords: Chinese Culture, Phonetic Symbol, Homophone, Animal’s Name, Chinese Language.